Local scours around side-weirs located on alluvial bends - Onen, Fevzi; Agaccioglu, Hayrullah (TURKISH CHAMBER CIVIL ENGINEERS, 2007)
An experimental investigation of the local depth of scour around the side-weirs located on the curved part of an alluvial channel, for sharp crested side weirs under subcritical flow condition is presented in this paper. At the downstream end of the side weir, a longitudinal bar in the middle of the channel and a scour hole close to the outer bank are formed because of the changes in the shear stress field and velocities. The depth of clear-water scour approaches asymptotically to equilibrium with time depending on the flow intensity. It is also found that the equilibrium depth of the scour depends on the dimensionless parameters of flow intensity, flow shallowness, weir crest height, side-weir length and bend angles. Although there is no scour for flow intensities less than 0.55, the equilibrium depth of scour increases almost linearly with increasing flow intensity and attains the maximum value at a depth when the flow intensity is equal to 1.0. The equilibrium depth of the scour also increases when other dimensionless parameters (flow shallowness, weir crest height and side-weir length) increase. In a curved channel, the equilibrium depth of the scour has the maximum value at theta=30 degrees, and the minimum value at theta = 120 degrees and 150 degrees sections of the bend
Keywords: BRIDGE PIERS; CURVED CHANNEL; FLOW; Engineering